2012
DOI: 10.4102/ojvr.v79i2.478
|View full text |Cite
|
Sign up to set email alerts
|

Leptospirosis in South Africa

Abstract: Leptospirosis is a common zoonosis worldwide. It has a ubiquitous distribution and causes a wide spectrum of disease. Leptospirosis therefore has a broad reservoir host range, and many infected species of animals excrete leptospires in their urine, which leads to contamination of soil and water. Typical descriptions of the disease include a biphasic (anicteric form) and fulminant disease in the icterohaemorrhagic form. Only a few local case reports of human leptospirosis have been published, the most recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The study has found that the apparent incidence of leptospirosis in the South African human population is moderately high based on the detected positives in suspected cases. The study also found that the communities in informal settlements in urban areas are at risk as infected rodent populations are a continuous source of transmission (Saif et al 2012). However this study could not establish which serovars were present.…”
Section: Leptospirosis In Humansmentioning
confidence: 77%
See 2 more Smart Citations
“…The study has found that the apparent incidence of leptospirosis in the South African human population is moderately high based on the detected positives in suspected cases. The study also found that the communities in informal settlements in urban areas are at risk as infected rodent populations are a continuous source of transmission (Saif et al 2012). However this study could not establish which serovars were present.…”
Section: Leptospirosis In Humansmentioning
confidence: 77%
“…In South Africa, rodents were also reported to be the main risk factor of human leptospirosis. In a study published in 2012, it was found that communities in informal settlements in urban areas are at risk as infected rodent populations are a continuous source of transmission (Saif et al 2012). The apparent incidence of leptospirosis in the South African human population was also found to be moderately high (Saif et al 2012).…”
Section: Management Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of human leptospirosis in South Africa has been suggested to be moderately high within the population [21][22][23]. Findings about the continued circulation of highly pathogenic Leptospira spp.…”
Section: Introductionmentioning
confidence: 99%
“…Weak diagnostic capacity and notification systems appear to contribute to a lack of accurate health surveillance data in many developing countries (Pappas et al., ). Indeed, a review of the literature returns just a handful of sporadic case reports, outbreaks and serosurveys of human leptospirosis from countries across the African continent (Mailloux et al., ; Sankale et al., ; Cacciapuoti et al., ; Turner and Willcox, ; Pinn, ; Onyemelukwe, ; Collares‐Pereira et al., ; Bertherat et al., ; WHO, ; Schoonman and Swai, ; Saif et al., ). Outside of a single case of leptospirosis reported in a cow ( L. interrogans serovar Pomona) in eastern Botswana over a quarter of a century ago (Herr and Winnen, ), there is no information regarding the occurrence of this important zoonotic pathogen in the country.…”
Section: Introductionmentioning
confidence: 99%